Impulsivity Derived From the Dark Side: Neurocircuits That Contribute to Negative Urgency - Zorrilla, Eric P.; Koob, George F. (Frontiers in Behavioral Neuroscience, 2019)
Negative urgency is a unique dimension of impulsivity that involves acting rashly when in extreme distress and impairments in inhibitory control. It has been hypothesized to derive from stress that is related to negative emotional states that are experienced during the withdrawal/negative affect stage of the addiction cycle. Classically, a transition to compulsive drug use prevents or relieves negative emotional states that result from abstinence or stressful environmental circumstances. Recent work suggests that this shift to the “dark side” is also implicated in impulsive use that derives from negative urgency. Stress and anxious, depressed, and irritable mood have high comorbidity with addiction. They may trigger bouts of drug seeking in humans via both negative reinforcement and negative urgency. The neurocircuitry that has been identified in the “dark side” of addiction involves key neuropeptides in the central extended amygdala, including corticotropin-releasing factor. The present review summarizes empirical and conceptual advances in the field to understand the role of the “dark side” in driving the risky and detrimental substance use that is associated with negative urgency in addiction.